Capecitabine metronomic chemotherapy for metastatic colorectal cancer patients reaching NED: A protocol for a prospective, randomized, controlled trial. - Jiaming Wu; Yu Dong; Wanshan Zhu; Jincheng Meng; Huatang Zhang; Cantu Fang; Lizhu Lin (PLoS ONE)
Introduction An increasing number of patients with metastatic colorectal cancer (mCRC) have achieved no evidence of diseases (NED) status after surgery or other treatments. However, the latest guidelines for colorectal cancer do not recommend an appropriate treatment for patients with mCRC who achieve NED status. Capecitabine metronomic chemotherapy has the advantages of significant efficacy and minimal adverse reactions, it is a potential effective method for maintenance treatment for mCRC, but no RCTs have been reported. Therefore, we designed a randomized controlled trial to evaluate the efficacy and safety of capecitabine metronomic chemotherapy for mCRC patients who achieve NED. Methods/design This study is a prospective, randomized controlled study that evaluates the efficacy and safety of capecitabine metronomic chemotherapy for patients with mCRC who achieve NED status. 240 eligible participants will be randomly assigned to either a capecitabine metronomic chemotherapy group or a "watch and wait" group at a 1:1 allocation ratio. Eligible patients diagnosed with stage IV mCRC, both the primary tumor and the metastases, are those who have achieved R0 resection (or complete destruction by ablation) and reached NED. Participants who are enrolled in the capecitabine group will receive capecitabine (500 mg/m2 body surface area twice daily) for 2 years. Meanwhile, those who are assigned to the control group will receive regular imaging examination and follow-up only. All participants will follow up for 1 year after receiving 2 years of intervention. The primary outcomes will be disease-free survival (DFS) from randomization, stratified by preoperative chemotherapy, metastatic organs, number of metastases, lenght of previous systemic treatment, response to previous chemotherapy. Secondary outcomes will include overall survival (OS), 1-year,2-year,3-year survival rate and adverse reactions. Discussion As a potentially effective treatment, low-dose capecitabine metronomic chemotherapy has been explored in clinical practice. The results of this trial will provide evidence on the efficacy and safety of capecitabine metronomic chemotherapy for patients with mCRC who have reached NED status. Trial registration Chinese Clinical Trial Registry (ChiCTR2100047149, protocol version number F2.0).